Academic research values: Conceptualization and initial steps of scale development - Andrea Kis; Elena M. Tur; Krist Vaesen; Wybo Houkes; Daniël Lakens (PLoS ONE, 2025)
We draw on value theory in social psychology to conceptualize the range of motives that can influence researchers’ attitudes, decisions, and actions. To conceptualize academic research values, we integrate theoretical insights from the literature on personal, work, and scientific work values, as well as the outcome of interviews and a survey among 255 participants about values relating to academic research. Finally, we propose a total of 246 academic research value items spread over 11 dimensions and 34 sub-themes. We relate our conceptualization and proposed items to existing work and provide recommendations for future scale development. Gaining a better understanding of researchers’ different values can improve careers in science, attract a more diverse range of people to enter science, and elucidate some of the mechanisms that lead to both exemplary and questionable scientific practices.